(untitled) (Bangladesh Journal of Medical Science, 2024)
Introduction Obesity has became a significant health concern over the past decade. According to a higher body mass index (BMI), obesity enhances the probability of malignancy, type 2 diabetes mellitus, cardiac disorders, and musculoskeletal diseases. Bariatric surgery, a typical and effective surgical intervention for patients with excess body weight with concurrent medical conditions, achieves significant weight loss over a long period. Numerous studies have been conducted on the effectiveness of various bariatric surgery techniques for improving glycemic homeostasis and helping patients lose weight. However, little is known about how bariatric surgery affects the lipid profile. The study aims to determine how patients’ altered BMI affects lipid parameters following OAGB/MGB surgery. Methods To achieve this, the longitudinal observational study was conducted from January 2021 to January 2022 among 150 patients scheduled to undergo Anastomosis Gastric Bypass Surgery. The mean age of the patients was 41.7 years, with a standard deviation of 14.7 years (mean±SD: 41.7±14.7). Among the study participants, 56 individuals (37.3%) were male, while 94 (62.7%) were female. Objectives Regarding comorbidities, hypertension was identified as the most prevalent condition among the enrolled patients, affecting 49.3% of them. Results It was observed that the levels of S. Cholesterol and S. Triglyceride showed a significant decrease after one month (Visit-1) of the bypass surgery, with a reduction of 21.8 mg/dl (95% CI=-31.9, -11.6, p=<0.001) and 14 mg/dl (95% CI=-25.5, -2.51, p=0.017), respectively Conclusion OAGB outcome is associated with a healthier lipid profile and enhanced weight management. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 327-336